(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Melioidosis is known endemic in many Southeast Asian countries, especially Thailand, and in Northern Australia. The disease was long considered under-recognized in India but has now gained the status of emerging infectious disease here. Increasing isolation of the causitive agent B. pseudomallei is encountered in the recent years from this part of western coastal India. We report one such case of pulmonary melioidosis in an elderly patient misdiagnosed as tuberculosis ending fatally. Prompt microbiological diagnosis prevents the unnecessary Anti-TB treatment or prophylaxis. This was also our first of isolation of B. pseudomallei from endotracheal aspirate. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 15-18 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7973